TINJAUAN FIKIH KONTEMPORER TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM KEHIDUPAN UMAT ISLAM - Muhammad Fauzi Al Ghifari; Anugerah Dimas Saputra; Muhammad Ramdan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The rapid advancement of Artificial Intelligence (AI) technology has significantly influenced various aspects of human life, including the Muslim community. AI is increasingly applied in education, economic activities, healthcare services, Islamic preaching, and other social domains. Nevertheless, its development has also generated several contemporary Islamic legal issues that require critical examination, including ethical considerations, the reliability of AI-generated information, personal data protection, intellectual property rights, and their compatibility with Islamic teachings. This study aims to explore the use of Artificial Intelligence in Muslim society from the perspective of contemporary Islamic jurisprudence. The research adopts a qualitative approach through library research by reviewing classical and modern fiqh literature, religious fatwas, and academic publications related to AI technology. The findings reveal that the application of AI is generally permissible in Islam, provided that it serves the public good (maslahah), avoids prohibited elements, does not result in harm, and adheres to the principles of Islamic law. Viewed through the framework of maqāṣid al-sharī‘ah, AI has the potential to contribute positively to societal development and the welfare of Muslims when implemented ethically and responsibly. Consequently, strengthening digital literacy and enhancing understanding of Islamic jurisprudence are essential to ensure that AI is utilized in a manner consistent with Islamic values